The uncrowned “Bohemian king” and his “bible” castle. Blatná as commisioned by the highest burgrave of Prague castle, Zdeňek Lev of Rožmitál, around the years 1520–1530 - Czechowicz, Bogusław (Res Gestae. Czasopismo historyczne, 2023)
This article presents a new interpretation of the ideological message of Blatná Castle after its expansion by Benedikt Ried, commissioned by Zdeňek Lev of Rožmitál around 1520-1530. The key to deciphering the biblical code of the residence of this powerful magnate is found in two columns standing in front of the castle façade, which have not been included in previous research. Their dilapidated state, as well as residually legible profile forms and ornaments, un equivocally point to their dating back to the time of Ried’s expansion. In the history of art, they are a well- known imitation of the bronze pillars of Jachin and Boaz, placed in front of the Old Testament Temple of Solomon. The expressive oriels of the part of the castle erected by Ried may be a reference to a diagram similar to a pentagram, often appearing on the pages of codices called the clavicula Salomonis. In the beginning, they contained the instructions of the great biblical king to his son Roboam. This is reflected in the family situation of the builder, as it is generally agreed that Blatná Castle was built by Zdeněk Lev in connection with the marriage of his son Adam. References to Solomon were quite common at the time, both at Prague Castle and at the residences of several Silesian dukes. They should not be surprising in the case of someone who, for more than 20 years (1507-1530), was the most important person in the state after the ruler (the highest burgrave of Prague Castle). Zdeněk Lev was a very active and influential politician with a Catholic orientation and nationalist, Bohemian disposition, who liked to moralize and judge and use biblical examples or episodes from Bohemian history.